2019
DOI: 10.1016/s2214-109x(19)30091-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and gender-based violence in camps for internally displaced people and host communities in northeast Nigeria: a mixed methods study

Abstract: Background The northeastern region of Nigeria has had a persistent increase in the number of internally displaced people due to insurgency. The disruption to the socioeconomic lives of the women in this region places them at a high risk of all forms of abuse from insurgents, security agents deployed to protect the people in the camps and host communities, and other members of the community. This study aims to assess the prevalence and pattern related to sexual and gender-based violence in selected states in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In contrast to the reported nature of violence during conflict, more than 92% of reported GBV post-conflict were attributable to sexual violence. This is consistent with reports of similar studies which indicate that sexual violence is a common feature of post-conflict insurgency in Nigeria (Ojengbede et al, 2019;Read, 2020). Sexual violence as epitomized by rape and sexual harassment were the main features of GBV reported by the participants post-conflict.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to the reported nature of violence during conflict, more than 92% of reported GBV post-conflict were attributable to sexual violence. This is consistent with reports of similar studies which indicate that sexual violence is a common feature of post-conflict insurgency in Nigeria (Ojengbede et al, 2019;Read, 2020). Sexual violence as epitomized by rape and sexual harassment were the main features of GBV reported by the participants post-conflict.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies focused only on either GBV experiences during conflict or post conflict (Aham-Chiabuotu, 2019; Anastario et al, 2009; Hynes et al, 2004; Logie et al, 2017). A recent descriptive study that included community members adopted a mixed-method approach to report prevalence and pattern of sexual and GBV in North-East Nigeria (Ojengbede et al, 2019). However, much remains to be understood about the nature of violence experienced by women during conflict, when in transit and after they have been lodged in internally displaced camps the country.…”
Section: Introductionmentioning
confidence: 99%
“…For ethical reasons we did not ask direct questions related to individuals’ personal experience of violence perpetrated by family members, community members, or by parties to the Boko Haram insurgency. As a result, our findings do not include reference to non-partner sexual violence, female genital mutilation/cutting, or forced or early child marriage although existing data indicate these forms of violence are relatively prevalent for adolescent girls in northeast Nigeria [ 46 , 80 , 81 ]. A third limitation of this research was that data from adolescent girl participants was limited; this was likely due to challenges the research team encountered in remotely training data collectors on the use of adolescent-friendly, participatory methodologies with younger adolescents (age 14 and under).…”
Section: Discussionmentioning
confidence: 99%
“…Given the diverse ways in which women in northeast Nigeria engage with the ongoing social and political conflict, they may be cast as sympathetic or complicit with Boko Haram by Nigerian state forces or community members, and be victimized as a result. A recent study found that among a sample of 4,868 adult women from across northeast Nigeria, including Borno State, 33% reported experiencing sexual violence; perpetrators included Boko Haram insurgents, members of police or other security forces, unknown individuals within the community, and intimate partners [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Women and girls have been identified to be even more vulnerable to GBV during moments of social disruption and insecurity. A survey among thousands of internally displaced persons in northern Nigeria reported that around a third and a fifth had been subjected to sexual and physical violence, respectively since their displacement 10 . The COVID-19 pandemic has been reported to have ripple effects on GBV, particularly in areas where insecurity and social inequality are persistent 11 .…”
Section: Introductionmentioning
confidence: 99%